Judeo-Christian perspectives on psychology : human nature, motivation, and change - Miller, William R. (William Richard); Delaney, Harold D. (Washington : American Psychological Association, 2005)
"Comparing and contrasting notions of humankind, chapter authors critically examine the current scientific focus in psychology on determinants of animal and human behavior and discuss how psychological research and practice might differ if informed by theistic perspectives."--BOOK JACKET.
Ch. 1. What is human nature? : reflections from Judeo-Christian perspectives / William R. Miller -- Ch. 2. Psychology's roots : a brief history of the influence of Judeo-Christian perspectives / Harold D. Delaney and Carlo C. DiClemente -- Ch. 3. Self and volition / Roy F. Baumeister -- Ch. 4. The relational self : psychological and theological perspectives / C. Stephen Evans -- Ch. 5. Story and narrative / Thomas H. Bien -- Ch. 6. The role of sexuality in personhood : an integrative exploration / Stanton L. Jones and Heather R. Hostler -- Ch. 7. The meaning that religion offers and the motivation that may result / Martin L. Maehr -- Ch. 8. Virtues, vices, and character education / Everett L. Worthington, Jr. and Jack W. Berry -- Ch. 9. Transformational change / Stephanie Brown and William R. Miller -- Ch. 10. Emerging models of spiritual development : a foundation for mature, moral, and health-promoting behavior / Jared D. Kass and Susan Lennox -- Ch. 11. The effects of religious practices : a focus on health / Carl E. Thoresen, Doug Oman and Alex H. S. Harris -- Ch. 12. Intergenerational transmission of religiousness and spirituality / Brenda A. Miller -- Ch. 13. Spiritual struggle : a phenomenon of interest to psychology and religion / Kenneth I. Pargament, Nichole A. Murray-Swank, Gina M. Magyar and Gene G. Ano -- Ch. 14. Implications of Judeo-Christian views of human nature, motivation, and change for the science and practice of psychology / Carlo C. DiClemente and Harold D. Delaney -- Ch. 15. Psychology as the science of human nature : reflections and research directions / William R. Miller and Harold D. Delaney.
Includes bibliographical references and indexes.
Keywords: Psychology and religion; Judaism and psychology; Christianity -- Psychology